Analysis Of The Effect Of Slope Of The Scratch Side Angle Through The Post Tool On Surface Level Surface At The Working Tool Stermination ST 37 - Muhammad Farid Riza; Yufrizal A; Nofri Helmi (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2019)
The purpose of this research is to see the effect of slope of incision angle chisel through Tool Post to roughness of surface of object. The method used is a lathe ST 37, with 0.5 mm cutting depth, with side angle cutting angle by tilting the Post Tool, ie: 10˚ tilted to the left, 10˚ tilted right, 0˚ (perpendicular), 5˚ tilted right, and 5˚ tilted left. Feeding (constant feeding) is: 0.281 mm / rotation, main cutting corner of chisel 80˚ and cutting speed = 740 rpm. Then the workpiece measured the surface roughness by using Surface Tester Mitutoyo SJ-201P. The result showed that, the smallest surface roughness rate achieved was (ΣRap) = 7, 42 μm with N9 surface roughness class with the Post Tool angle 5 ° to the left. While the largest surface roughness rate achieved is (ΣRap) = 13, 76 μm with the surface roughness class N11 with the tool angle post 10 ° to the right. The value of the roughness level achieved is between N9 - N11.